INNOVATIVE APPROACHES IN SPORTS PEDAGOGY AND THEIR EFFECTIVENESS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
In recent years, sports pedagogy has undergone a profound transformation as a result of the integration of innovative teaching strategies and technological advancements. These developments have reshaped the way physical education and athletic training are conceptualized, delivered, and assessed, with a growing emphasis on learner-centered, interactive, and evidence-based methods. The purpose of this study is to explore the various innovative approaches currently being applied in sports pedagogy and to evaluate their impact on learners’ physical, cognitive, and motivational outcomes. The article examines key innovations such as digital learning platforms, gamification in physical education, blended learning models, virtual and augmented reality in skill acquisition, as well as data-driven coaching methods. These pedagogical strategies have been shown to enhance student engagement, improve skill retention, promote autonomous learning, and foster greater inclusivity in the learning environment. Special attention is given to the role of formative assessment tools, mobile fitness applications, wearable technologies, and AI-assisted performance tracking, which have revolutionized how progress and performance are measured in both academic and athletic settings. Furthermore, the effectiveness of these innovations is evaluated through empirical research and case studies conducted in schools, universities, and sports academies. The findings suggest that when applied appropriately, innovative approaches contribute to more personalized, flexible, and adaptive educational environments, which in turn positively influence learning efficiency, discipline-specific competence, and long-term athletic development.The study also addresses potential barriers to innovation, including limited access to technology, lack of teacher training, resistance to change, and the digital divide among different regions and institutions. In conclusion, the article advocates for a systematic integration of innovation in sports pedagogy supported by policy reforms, continuous professional development, and cross-sector collaboration between educators, technologists, and sports scientists.